2022
DOI: 10.1177/23792981221096871
|View full text |Cite
|
Sign up to set email alerts
|

For You? Using TikTok® to Teach Key Content

Abstract: As management educators grapple with the challenges of educating Gen Z cohorts (born 1997–2015) in and beyond an online COVID-19 environment, social media platforms represent potential teaching tools. TikTok® is one of the most popular global social media technologies with people aged under 25 and therefore has strong appeal for students. TikTok allows users to view and create short video content of 3 minutes or less for a range of purposes, including education. This review details how TikTok was used to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Research into its educational potential reveals that TikTok uniquely caters to the preferences of Gen Z students, offering an engaging and relevant way to deliver educational content across various disciplines including management education, special education, and speech-language pathology. Middleton (2022) demonstrates how TikTok complements traditional teaching methods in undergraduate courses, enhancing engagement through its familiar, multimedia approach (Middleton, 2022) Also, a duoethnographic study in higher education revealed that TikTok could facilitate a posthuman educational encounter, which blends human and non-human elements in teaching and learning, thereby enhancing the educational experience in diverse international settings (Heyang & Martin, 2022).…”
Section: Tiktok's Emergence As An Educational Platformmentioning
confidence: 99%
“…Research into its educational potential reveals that TikTok uniquely caters to the preferences of Gen Z students, offering an engaging and relevant way to deliver educational content across various disciplines including management education, special education, and speech-language pathology. Middleton (2022) demonstrates how TikTok complements traditional teaching methods in undergraduate courses, enhancing engagement through its familiar, multimedia approach (Middleton, 2022) Also, a duoethnographic study in higher education revealed that TikTok could facilitate a posthuman educational encounter, which blends human and non-human elements in teaching and learning, thereby enhancing the educational experience in diverse international settings (Heyang & Martin, 2022).…”
Section: Tiktok's Emergence As An Educational Platformmentioning
confidence: 99%
“…Due to the individual's success in creating videos, there were TikTok celebrities even in Indonesia [10][11][12]. This platform promotes the Challenge as a draw for users to want to utilize TikTok [13]. This portal promotes the Challenge initiative [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These earlier works on technology in the classroom have been followed by several more Management Teaching Review (MTR) articles examining technology. Topics that MTR authors have addressed include engaging applications, such as TikTok (Middleton, 2022), helping with application of project-based learning concepts (Jackson & Halbert, 2021), and even conducting remote oral doctoral defenses (Allen & Williams, 2022).…”
mentioning
confidence: 99%